2015
DOI: 10.1103/physrevb.92.235153
|View full text |Cite
|
Sign up to set email alerts
|

Charge density wave in layeredLa1xCexSb2

Abstract: The layered rare-earth diantimonides RSb 2 are anisotropic metals with generally low electronic densities whose properties can be modified by substituting the rare earth. LaSb 2 is a nonmagnetic metal with a low residual resistivity presenting a low-temperature magnetoresistance that does not saturate with the magnetic field. It has been proposed that the latter can be associated to a charge density wave (CDW), but no CDW has yet been found. Here we find a kink in the resistivity above room temperature in LaSb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 65 publications
(90 reference statements)
8
28
0
Order By: Relevance
“…3,4,8,9 Recently, evidence of a CDW transition was observed and hypothesized to arise from stacking faults. 11 In the present study, we have observed an isotropic resistivity in the layers of an orthorhombic crystal. While this is physically possible, then it is unlikely considering the range of temperature and magnetic fields used here.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…3,4,8,9 Recently, evidence of a CDW transition was observed and hypothesized to arise from stacking faults. 11 In the present study, we have observed an isotropic resistivity in the layers of an orthorhombic crystal. While this is physically possible, then it is unlikely considering the range of temperature and magnetic fields used here.…”
Section: Discussionsupporting
confidence: 52%
“…The observed isotropy strongly suggests such mechanism to be at play. Furthermore, previous reports have also reported low crystal quality in the c-direction 6 and weak interlayer interaction, 3,4,[9][10][11] suggesting that this is a common feature of LaSb 2 crystals, especially when considering the good agreement between reported properties and RRRs. Another manifestation of the weak interaction between layers is that the irregularities between layers, be it twinning or stacking faults, has little to no influence on the in-plane crystallinity, which is evident from the high RRRs and long mean free path of the phonons and electrons.…”
Section: B Transport Propertiesmentioning
confidence: 73%
See 3 more Smart Citations